2011
DOI: 10.1038/aja.2011.76
|View full text |Cite
|
Sign up to set email alerts
|

Effects of di-n-butyl phthalate on male rat reproduction following pubertal exposure

Abstract: Di-n-butyl phthalate (DBP) is an endocrine-disrupting chemical that has the potential to affect male reproduction. However, the reproductive effects of low-dose DBP are still not well known, especially at the molecular level. In the present study, pubertal male Sprague-Dawley rats were orally administered DBP at a wide range of doses (0.1, 1.0, 10, 100 and 500 mg kg⁻¹ day⁻¹) for 30 days. The selected end points included reproductive organ weights, testicular histopathology and serum hormonal levels. Additional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
38
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 47 publications
6
38
1
Order By: Relevance
“…Similar observations were reported by Zhou et al (2010) where activities of SOD decreased at 250 and 500 mg/kg/day DBP, although increase was also reported after 100 mg/kg/day. Contrary to the present study, increased expression of oxidative stress protein SOD1 (Cu-ZnSOD) after exposure to DBP (0.1, 1.0, 10, 100, and 500 mg/kg/day) for 30 days was reported (Bao et al 2011). Catalase and glutathione peroxidase/reductase (GPx/GR) system are known scavengers for ROS.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Similar observations were reported by Zhou et al (2010) where activities of SOD decreased at 250 and 500 mg/kg/day DBP, although increase was also reported after 100 mg/kg/day. Contrary to the present study, increased expression of oxidative stress protein SOD1 (Cu-ZnSOD) after exposure to DBP (0.1, 1.0, 10, 100, and 500 mg/kg/day) for 30 days was reported (Bao et al 2011). Catalase and glutathione peroxidase/reductase (GPx/GR) system are known scavengers for ROS.…”
Section: Discussioncontrasting
confidence: 77%
“…Generation of free radicals (O 2 ·ˉ, OH·, or O·) causes lipid peroxidation leading to oxidative stress overwhelming the antioxidant defense system (Halliwell 2011). Proteomic analysis of testes revealed 20 differentially expressed proteins with 12 proteins involved in cell cycle, spermatogenesis as well as oxidative stress (Bao et al 2011). The expressions of these proteins were affected at low dose of DBP.…”
Section: Introductionmentioning
confidence: 98%
“…The results of our study indicate that NP, DBP and BPA alone basically have detrimental effects. These results are consistent with previous studies (Hunt et al, 2003;Gang and Han, 2006;El-Dakdoky and Helal, 2007;Hallmark et al, 2007;Gong et al, 2009;Bao et al, 2011). The present study attempted to evaluate the combination effects of low and high dose mixtures of NP, DBP and BPA on boar sperm characteristics.…”
Section: Discussionsupporting
confidence: 81%
“…DBP and DEHP have been shown to affect the structures and functions of Sertoli cells and germ cells in rats, resulting in a decrease in the number of Sertoli cells and secretion of testosterone hormone in the testes. Together with the decrease in testosterone, the dysfunction and decreased number of Sertoli cells results in a reduction in the number of spermatogenic cells (Bao et al, 2011) and premature detachment of round spermatids (Erkekoglu et al, 2011;O'Donnell et al, 1996), consequently reducing sperm production or increasing abnormal sperm morphology. In agreement with our findings, some studies of rats have reported adverse effects of DBP exposure on sperm production (Bao et al, 2011;Foster et al, 2001) and of DEHP on sperm morphology (Agarwal et al, 1985;Erkekoglu et al, 2011).…”
Section: Discussionmentioning
confidence: 98%